Implementasi Sosial Media Dan Festival Agro Wisata Untuk Meningkatkan Penjualan Durian Dan Olahan Ketela Candimulyo Magelang Menggunakan Strategi Marketing 10P - Rokhaniyah, Siti; Nilasari, Ayunda Putri; Retnosari, Retnosari; Astutik, Erni Puji; Fahadha, Rizqa Ula; Tyasningwuri, Elisabeth Meidiana; Mukaromah, Fili (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2023)
This study aims to measure the effectiveness of implementing social media to increase sales of durian and processed cassava in Candimulyo District, Magelang Regency using the 10P marketing strategy. This is a field research, with primary data from interviews and distributing questionnaires. The sample consisted of 40 sellers of durian and processed cassava. Data analysis was carried out by validity and reliability test, t-test, N-gain formula, multiple regression analysis, and analysis of qualitative data to strengthen the results of quantitative analysis. The results of the data analysis show: 1) there is a difference in the nominal income in the conditions before and after the implementation of the 10P marketing strategy 2) the implementation of the 10P marketing strategy to increase income is quite effective (moderate effectiveness category) 3) of the 10 elements of the 10P marketing mix, 8 of them has a positive effect on increasing income (product, promotion, professional, people, public, power, pressure, and performance), while price and place, statistically, have no effect on income 4) agro-tourism festivals are quite effective as media promotions and efforts to increase durian sales 5) social media is the most popular means of promotion, because of its convenience and affordability.